Music Therapy. - Bunt, Leslie (London : Routledge, 1994)
This text aims to explain music therapy's history, uses, relationship to other therapeutic techniques and clinical bases. Examples from work with adults and children demonstrate a synthesis between art and science.
Keywords: Music therapy